Marine Bacteria with antimicrobials capacity isolated from cultures of bivalve mollusks - Pellon, Fabiola (2001)
Microorganisms have commonly been studied as producers of antibacterial substances; yet they are also considered producers of antifungic, antiviral, antiparasitic, citotoxics and inhibitory of other forms of cellular growth substances. This paper describes the isolation, inhibitory potential and phenotipic characterization of native bacterial strains associated to bivalve mollusks such as Argopecten purpuratus “concha de abanico” and Crassostrea gigas “ostra” in cultivation systems. From 345 marine strains collected, 20 strains were recovered that had the ability of inhibiting a wide spectrum of fish, mollusks and shellfish pathogenic bacteria; being the most sensitive pathogens Aeromonas sobria P-281, Aeromonas hydrophila ATCC 7966, Vibrio vulnificus ATCC 27562 and Vibrio parahaemolyticus ATCC 17803. The phenotipic characterization of this strains with inhibitory capacity allowed the identification of the following genera: Vibrio (40%), Aeromonas (15%), Flavobacterium (10%), Pseudomonas (5%), Moraxella (5%), Flexibacter (5%). A 20% could not be identified. The results suggest that the isolated bacteria could be used as probiotics agents for the biological control of pathogens from marine organisms of interest in mariculture.